Encapsulation Characteristic of Bougainvillea (Bougainvillea glabra) Dye Extract in Comparison of Maltodextrin and Carrageenan - Wartini, Ni Made; Gunam, Ida Bagus Wayan; Ganda Putra, Gusti Putu; Nara Swari, Luh Sri (Trends in Sciences, 2024)
Bougainvillea flower is recognized as food coloring agent due to the presence of betacyanin compounds. The extraction of these compounds is followed by a subsequent process for encapsulation. Therefore, this research aimed to determine the effect of maltodextrin and carrageenan on encapsulation characteristics of bougainvillea flower dye extract and obtain the best ratio. Encapsulation was carried out with the ratio of maltodextrin and carrageenan, namely 10:0 (MC1), 9.5:0.5 (MC2), 9:1 (MC3), 8.5:1.5 (MC4), 8:2 (MC5) and 7.5:2.5 (MC6). The results showed that maltodextrin and carrageenan ratio significantly affected the amendment, moisture content, solubility, brightness level (L*), redness level (a*), yellowness level (b*), total betacyanin, surface betacyanin and encapsulation efficiency. Based on the test, the effectiveness index to produce the best treatment was MC3 with characteristics of amendment, moisture content, solubility, brightness level (L*), redness level (a*), yellowness level (b*), total betacyanin, surface betacyanin and encapsulation efficiency at 91.61 ± 0.34, 6.53 ± 0.22, 87.35 ± 1.90 %, 80.43 ± 1.37, 20.37 ± 0.49, 20.73 ± 0.40, 246.99 ± 2.70, 35.76 ± 0.46 mg/100 g and 85.52 ± 0.09 %, respectively. The encapsulated formulation of bougainvillea flower extract with maltodextrin and carrageenan in a balanced ratio can be used as an alternative to provide natural coloring in food processing. HIGHLIGHTS Bougainvillea flowers can be extracted to produce an extract containing betacyanin Bougainvillea extract is liquid and is easily damaged by oxidation Application of encapsulation in bougainvillea extract can protect betacyanin from damage due to oxidation and hydrolysis, evaporation or heat degradation The novelty in this research is the optimal treatment for producing encapsulated natural bougainvillea flower dye extract is a ratio of maltodextrin and carrageenan of 9:1. The formulation of bougainvillea flower extract with maltodextrin and carrageenan in an appropriate ratio can be used as a potential natural coloring alternative in functional food processing. GRAPHICAL ABSTRACT